2024
DOI: 10.1001/jamaneurol.2024.0221
|View full text |Cite
|
Sign up to set email alerts
|

Time to Anticoagulation Reversal and Outcomes After Intracerebral Hemorrhage

Kevin N. Sheth,
Nicole Solomon,
Brooke Alhanti
et al.

Abstract: ImportanceIntracerebral hemorrhage (ICH) is the deadliest stroke subtype, and mortality rates are especially high in anticoagulation-associated ICH. Recently, specific anticoagulation reversal strategies have been developed, but it is not clear whether there is a time-dependent treatment effect for door-to-treatment (DTT) times in clinical practice.ObjectiveTo evaluate whether DTT time is associated with outcome among patients with anticoagulation-associated ICH treated with reversal interventions.Design, Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…24 One potential explanation for these findings in RACECAT was patients with ICH transferred to EVT-capable stroke centers may have had delayed emergency stabilization and ICH "bundle of care" measures as compared to patients directly transported to local stroke centers. Results from INTERACT3 7 and other literature 25 have recently demonstrated that early bundled care for ICH, including antithrombotic reversal, 8 appropriate management of blood pressure, hyperglycemia and pyrexia led to improved functional outcomes. 7 While we were unable to measure the presence or absence of ICH care bundles in the current study, one interpretation of our findings is that longer DIDO times at transferring facilities may have afforded more adequate time for emergency stabilization measures, which could have translated into better outcomes from ICH and SAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 One potential explanation for these findings in RACECAT was patients with ICH transferred to EVT-capable stroke centers may have had delayed emergency stabilization and ICH "bundle of care" measures as compared to patients directly transported to local stroke centers. Results from INTERACT3 7 and other literature 25 have recently demonstrated that early bundled care for ICH, including antithrombotic reversal, 8 appropriate management of blood pressure, hyperglycemia and pyrexia led to improved functional outcomes. 7 While we were unable to measure the presence or absence of ICH care bundles in the current study, one interpretation of our findings is that longer DIDO times at transferring facilities may have afforded more adequate time for emergency stabilization measures, which could have translated into better outcomes from ICH and SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Model covariates with missing data were imputed before entering into models following previous GWTG-stroke studies. 8,21 Observations with >25% missing were excluded and missing medical history values and medications prior to admission were imputed to “No”. Insurance status for patients 65 years or older was imputed to “Medicare” and all other patients were imputed to “Private / VA / Champus / Other Insurance”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The main goal of hyperacute treatment is to prevent secondary hematoma expansion. 7 Recent data suggest that faster delivery of anticoagulation reversal 8 and blood pressure control 9 are beneficial, thus fast and targeted treatment delivery is key to improve outcomes in intracerebral hemorrhage. 10 These measures are easy to deliver at a TSC/PSC and do not need the infrastructure of a CSC.…”
mentioning
confidence: 99%